Intracellular Electrochemical Nanomeasurements Reveal that Exocytosis of Molecules at Living Neurons is Subquantal and Complex. Issue 17 (3rd March 2020) - Larsson, Anna; Majdi, Soodabeh; Oleinick, Alexander; Svir, Irina; Dunevall, Johan; Amatore, Christian; Ewing, Andrew G.
Abstract: Since the early work of Bernard Katz, the process of cellular chemical communication through exocytosis, quantal release, has been considered to be all or none. Recent evidence has shown exocytosis to be partial or "subquantal" at single‐cell model systems, but there is a need to understand this at communicating nerve cells. Partial release allows nerve cells to control the signal at the site of release during individual events, for which the smaller the fraction released, the greater the range of regulation. Herein, we show that the fraction of the vesicular octopamine content released from a living Drosophila larval neuromuscular neuron is very small. The percentage of released molecules was found to be only 4.5 % for simple events and 10.7 % for complex (i.e., oscillating or flickering) events. This large content, combined with partial release controlled by fluctuations of the fusion pore, offers presynaptic plasticity that can be widely regulated. Abstract : Partial chemical release : Partial chemical release allows nerve cells to control the signal at the site of release during individual events, in which the smaller the fraction released, the greater the range of regulation. Intracellular electrochemistry at a nanotip electrode combined with theoretical modeling shows that the vesicular octopamine content is very large and the exocytotic fraction released from a living Drosophila larval neuro‐muscular neuron is very small.